Quantitative Determination of Azithromycin in Human Plasma by Liquid ChromatographyMass Spectrometry and its Application in Pharmackokinetic Study (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Azithromycin is an effective and well-known antimicrobial agent. In the present study, a simple, sensitive and specific LC/MS/MS method has been developed and validated for the quantification of Azithromycin in  human serum samples using Clarithromycin as internal standard. Azithromycin was extracted from biological matrix  by using solid phase extraction process. The chromatographic separation was performed on Luna C18 (3 ?, 2x150   mm) column with a mobile phase consisting of 35 mM ammonium acetate buffer (mobile phase-A) and acetonitrile  and methanol in ratio of 90:10 ( as mobile phase-B) at a flow rate of 0.25 mL/min. The method was validated over a  linear concentration range of 0.5?50.0 ng/mL and limit of quantification (LOQ) was 0.5 ng/mL with a coefficient of  correlation (r2) = 0.9998. The intra-day and inter-day precision expressed as relative standard deviation were 1.64% 8.43% and 2.32% 9.92%, respectively. The average recovery of azithromycin from serum was 98.11%. The method  was successfully applied to a pharmacokinetic study after oral administration of Azithromycin 200 mg/5 ml suspension in healthy Bangladeshi volunteers. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12488 Dhaka Univ. J. Pharm. Sci. 11(1): 55-63, 2012 (June)